Personality traits and sporting level of athletes - Paweł Adam Piepiora (Physical Education of Students)
Background and Study Aim. Personality traits significantly influence athletic performance and the development of athletes. However, these traits vary at different levels of sport. This knowledge gap makes it difficult to effectively tailor training and support programs. Thus, the purpose of this article is to identify differences in the expression of personality traits among professional athletes, competitive athletes, and amateur athletes.